PMS2 Expression With Combination of PD-L1 and TILs for Predicting Survival of Esophageal Squamous Cell Carcinoma - Jiang, Dongxian; Song, Qi; Wei, Xiaojun; Yu, Zixiang; Liu, Yufeng; Wang, Haixing; Wang, Xingxing; Huang, Jie; Su, Jieakesu; Hong, Yang; Xu, Yifan; Xu, Chen; et al. (Frontiers in Oncology, 2022)
Background DNA mismatch repair (MMR) deficiency (dMMR) has been recognized as an important biomarker for immunotherapy in esophageal squamous cell carcinoma (ESCC), along with programmed death ligand 1 (PD-L1) expression and/or tumor-infiltrated lymphocytes (TILs). However, in ESCC, MMR protein assessment has not been well studied at present. Methods A total of 484 ESCC tissues treated between 2007 and 2010, in our hospital, were enrolled. Immunohistochemical expression of MLH1, MSH2, MSH6, PMS2, and PD-L1 on tissue microarray specimens and clinicopathological features, including TILs, were analyzed retrospectively. Results Out of the 484 studied cases, loss of MLH1, MSH2, MSH6, and PMS2 expression were found in 6.8%, 2.1%, 8.7%, and 4.8% patients, respectively. dMMR was found in 65 patients, 37 cases involved in one MMR protein, 17 cases involved in two proteins, 7 cases involved in three proteins, and 4 cases involved in four proteins. There was no significant survival difference between pMMR (MMR-proficient) and dMMR patients (P>0.05). However, 224 patients with low PMS2 expression had better DFS and OS than 260 patients with high PMS2 expression (P=0.006 for DFS and 0.008 for OS), which was identified as an independent prognostic factor in multivariate analyses. Positive PD-L1 expression was detected in 341 (70.5%) samples. In stage I-II disease, patients with PD-L1 expression had better DFS and OS than those without PD-L1 expression(P<0.05), which was not found in stage III-IV disease. With the ITWG system, 40.1% of cases were classified as high TILs. Patients in the high-TILs group tended to have better DFS (P=0.055) and OS (P=0.070) than those in the low-TILs group and the differences were statistically significant in pMMR, high MSH6, or PMS2 expression cases (P<0.05). Also, high PMS2 expression patients with both PD-L1 expression and high TILs, had similar DFS and OS compared with low PMS2 expression patients (P>0.05), which were much better than other high PMS2 expression patients. Conclusion The expression level of MMR proteins could also be used as a prognostic factor in ESCC and PMS2 expression outperformed other MMR proteins for predicting survival. The combination of PD-L1 expression and TILs may lead to more efficient risk stratification of ESCC.